The Mists of Ramanna The Legend That Was Lower Burma - Aung-Thwin, Michael A. (University of Hawai'i Press, 2005)
Scholars have long accepted the belief that a Theravada Buddhist Mon kingdom, Ramannadesa, flourished in coastal Lower Burma until it was conquered in 1057 by King Aniruddha of Pagan-which then became, in essence, the new custodian and repository of Mon culture in the Upper Burmese interior. This scenario, which Aung-Thwin calls the ""Mon Paradigm,"" has circumscribed much of the scholarship on early Burma and significantly shaped the history of Southeast Asia for more than a century. Now, in a masterful reassessment of Burmese history, Michael Aung-Thwin reexamines the original contemporary accounts and sources without finding any evidence of an early Theravada Mon polity or a conquest by Aniruddha. The paradigm, he finds, cannot be sustained. Aung-Thwin meticulously traces the paradigm's creation to the merging of two temporally, causally, and contextually unrelated Mon and Burmese narratives.